ANALISIS KERAGAAN PERIKANAN TANGKAP DI KOTA TERNATE - Rommy M. Abdullah; Sugeng H. Wisudo; Daniel R. Monintja; M. Fedi A. Sondita (Institut Pertanian Bogor, 2011)
This research is aimed to identify the performance of capture fisheries in Ternate city. Performance of these include the development of number of capture fisheries households /RTP, fishing boats, fishing gear, fishing production, post-harvest handling, fishing areas and fishing seasons. The result showed that the average growth of number of capture fisheries households in Ternate city decreased by 2.67%. Fishing boats structure is still dominated by small-scale fisheries (87.85%). An average of amount fishing gears occurred in purse seine (24.55%/year). The development of average annual production of capture fisheries in ten last years increased by 14.61% to the type of fish caught are dominated by skipjack (Katsuwonus Pelamis). Post-harvest handling is fresh consumption (15.854,87 tonnes). Catching fish was conducted in the Maluku Sea (WPP 716) and season arrests were made throughout the year and peak season in January-April and September-October.